Modelling and Applying Learning Strategies in a Networked Higher Educational Context - Skiadelli, Maria; Sgouropoulou, Cleo; Maistros, Yanis (Proceedings of the International Conference on Networked Learning, 2008)
Within recent years great of effort has been put into the introduction of innovative instructional methods in higher education that incorporate the use of technology and cultivate skills considered as valuable for the learners of our era. Project Based Learning (PBL) is one of the most promising ones with regard to this requirement. IMS Learning Design is a specification used to describe learning scenarios. In IMS-LD the structure of the learning scenario is separated from the learning materials and services. The IMS LD specification is expressed as an XML binding which cannot be easily used by non-technical users such as teachers. Special tools have been created for this reason, which facilitate the learning design process (eg. the RELOAD editor). However the process of transforming a lesson plan from a simple narrative to a complete learning design is still not trivial and requires a deep knowledge of the specification itself. We claim that by providing teachers with pre-designed learning scenarios based on a concrete learning approach like PBL, we give teachers the opportunity to create their own learning designs in less time (accelerate the process) and allow them to focus on adjusting the core model to their own specific needs, adding their own resources and services. The methodology for the design of the PBL model has the following five steps: a. define the design requirements, b. decide the project set-up, c. write the first level narrative of the scenario in natural language, d. write the second level narrative using IMS-LD terminology in natural language, as well, e. design the graphical model in MOT+. MOT+ is an object-oriented modelling tool that it can also be used as a graphical IMS-LD editor providing all the elements of the IMS-LD information model and a set of semantic links for the representation of their relationships. The designed model can be exported in XML according to the IMS-LD XML binding. This is an important reason why we opt for using MOT+ instead of another general purpose modelling tool. Our model is based on learning patterns. According to the initial definition that Alexander gave: “A pattern is a solution to a problem that occurs in various contexts and can be reused ever and ever”. While writing the narrative of the PBL scenario, we noticed that there are several reoccurring situations that can be modelled in a similar manner. For instance the cycle “propose-negotiate-synthesize”, appears constantly in a PBL scenario whenever a decision has to be taken and therefore consensus is required. No matter if the members of the team have to choose their leader or make up their minds about the project milestones, or assign roles to individual members, they always have to follow the abovementioned activity cycle. These situations are not identical; there are a number of parameters that may vary (subject, time, place, outcome, etc.) but they all share a common core that can be identified as a good common practice or solution wherever the situation of reaching consensus arises. Therefore we claim that this activity cycle forms a pattern. After the identification and the design of patterns, we ended up with a list of six patterns that are used (and sometimes reused) in our PBL model and which can also be used in other PBL models based on different scenarios. The MOT+ models of these patterns can be exported in IMS-LD XML format, filled up with suitable resources and services (via an IMS-LD editor) and be played by an IMS-LD player as independent Units of Learning or combined together in a larger system setup. This task can be performed by instructors that they do not have any particular technical expertise or knowledge of the IMS-LD specification itself.